Validation of the P-POSSUM score in predicting outcomes in emergency craniotomy: A prospective observational study - Hari Prakash Rai; Shivam Sharma (Asian Journal of Medical Sciences, 2024)
Background: The Portsmouth physiological and operative severity score for the enumeration of mortality and morbidity (P-POSSUM) is an established tool for predicting surgical outcomes. However, its applicability and accuracy in predicting post-operative mortality in patients undergoing emergency craniotomy require further validation.